2023
DOI: 10.3389/fpsyt.2023.1050973
|View full text |Cite
|
Sign up to set email alerts
|

Animal studies reveal that the ghrelin pathway regulates alcohol-mediated responses

Abstract: Alcohol use disorder (AUD) is often described as repeated phases of binge drinking, compulsive alcohol-taking, craving for alcohol during withdrawal, and drinking with an aim to a reduce the negative consequences. Although multifaceted, alcohol-induced reward is one aspect influencing the former three of these. The neurobiological mechanisms regulating AUD processes are complex and one of these systems is the gut-brain peptide ghrelin. The vast physiological properties of ghrelin are mediated via growth hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Ghrelin not only enhances reinforcement learning of foodmediated rewards, but also affects the reinforcing properties of other substances like alcohol, cocaine, and heroin (for reviews, see [61][62][63]). Emerging work provides translational evidence supporting the same in people with addictive behaviors receiving either an IV ghrelin infusion or a GSHR blocker [54,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin not only enhances reinforcement learning of foodmediated rewards, but also affects the reinforcing properties of other substances like alcohol, cocaine, and heroin (for reviews, see [61][62][63]). Emerging work provides translational evidence supporting the same in people with addictive behaviors receiving either an IV ghrelin infusion or a GSHR blocker [54,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…While this system emerged as an important regulator of energy balance and body weight homeostasis [19] the evidence of the relationship between ghrelin/GHSR and alcohol consumption/seeking is growing (see [20] for review). Preclinical and clinical studies have highlighted a bidirectional relationship between exogenous ghrelin levels and alcohol consumption [20][21][22][23][24][25][26], and GHSR antagonists and inverse agonists have shown efficacy in reducing alcohol consumption when administered both peripherally and centrally [24,[27][28][29][30]. Further, recent clinical trials have shown safety, tolerability, and some efficacy of GHSR inverse agonist, PF-5190457, to reduce craving in heavy drinking individuals [31,32].…”
Section: Introductionmentioning
confidence: 99%